The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5116/ijme.4b97.d76a
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with first year medical students to improve Communication Skills teaching in The University of the West Indies

Abstract: Objectives: This paper reports first year Caribbean medical students' preferred and least preferred Communication Skills teaching styles. It also reports their views on assessment and what qualities they valued in a good Communication Skills teacher. Methods: Questionnaires were administered to first year students at the end of Semester One and the data compared with the results of a study using the same questionnaire format in the UK. Results: Caribbean medical students favoured interactive lectures with oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…Similar to previous studies 10,12 the students felt that experience in teaching field and personality was not an essential trait of the teacher. On the other hand, majority believed that ability to effectively communicate the details of topic being taught ranked highest among the qualities of an ideal teacher (71.9%) in addition to being knowledgeable and updated regarding the subject.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to previous studies 10,12 the students felt that experience in teaching field and personality was not an essential trait of the teacher. On the other hand, majority believed that ability to effectively communicate the details of topic being taught ranked highest among the qualities of an ideal teacher (71.9%) in addition to being knowledgeable and updated regarding the subject.…”
Section: Discussionsupporting
confidence: 83%
“…Comments on the same revealed that majority of them agreed that they need to devote less time to study outside the classroom. This was further supported by a similar study in China in which 89.4% of the respondents admitted that they prefer interactive session in terms of comprehension [11]. In contrast to our findings, Williams et al reported that first year medical students had learnt less in interactive session compared to lectures [12].…”
Section: Discussioncontrasting
confidence: 56%
“…In another study, 19.6% of first year Caribbean medical students chose student role-play as their least preferred communication teaching style 9 . Joyner and Young states that the reason medical students often dislike role plays could be because when role plays are unstructured and unplanned, active learning does not necessarily occur 10 .The present study was undertaken to determine the perceptions of first year medical students in an Indian medical college about the use of role-play in Physiology as a teaching-learning method.…”
Section: Introductionmentioning
confidence: 99%